Accelerated degree programs work best with deep relationships, trust. Issue 5 (10th January 2019) - Sutton, Halley
Abstract : Patricia Laprey, director of the accelerated degree program for adult learners at Ramapo College of New Jersey, worked as a secondary school teacher before finding her calling working with adult learners. "I really enjoy working with this age population so much more. They have so many resources and so many other supports and avenues — we have to really respect the very deliberate choice that an adult learner has made to go on this journey with us, with our institution, " Laprey said.